Necrotizing arteritis of the appendix - Ciudad Cavero, Adriana (1967)
In the pathological study of prophylactically removed appendices or appendicular present clinical pictures , you may find lesions of necrotizing arteritis. In 1932 , Plaut (13 ) described for the first time , this appendix necrotizing lesion at the level of small arteries and arterioles , as a specific and focal manifestation. From then until now , several authors have presented their contribution in this regard, sometimes describing the injury, individual personality , and others , relating more diffuse vascular disease , especially with polyarteritis nodosa . In our area have not reported similar findings to date , perhaps not considering them of significance for the elucidation of the problem of appendicitis or of arteritis. It is our purpose in this paper to present a review of the cases we found , the symptoms present , suggestive of appendiceal or suffering, and in pathological anatomic findings each . Chances are, with a more detailed aspect regarding the experimental study of this process , we can, in the future, to elucidate the pathogenesis of these lesions , their relationship with systemic boxes collagen disease or generalized arteritis, and tables allergic in nature.